Comparative performance analysis between open-source virtual firewalls - Fuentes, Regulus D., Jr. (Animo Repository, 2022)
Firewalls are considered as one of the major components in a network infrastructure that serves as the primary line of defense towards the possible occurrence of network attacks between and within private and public network environments. Integrated technologies that are associated with firewalls include packet filtering, data encryption and application detection schemes. The common measures being used in measuring its performance include its throughput capability, latency, and its resistance towards Denial-of-Service attacks. This was based on studies were conducted in relation to the performance analysis with various commercial and open-source firewall vendors using different architectures not limited to hardware, software, and virtual firewalls. Based on the conducted assessment using a similar test environment, each of the identified key metric was succeeded by a different open-source firewall. The overall throughput performance evaluation concluded that the IPFire firewall is the most capable of handling data in various data traffic ranges. The overall latency assessment determined that the PFSense firewall processes the lowest delay in line with the parallel generated throughput traffic. The third criterion which was the DoS resistance testing determined the capability of Untangle Next Generation firewall in resisting the attacks with the least firewall CPU utilization and having the lowest latency value and the highest ping success rate.